The practical art of suicide assessment : a guide for mental health professionals and substance abuse counselors - Shea, Shawn Christopher (Canada : John Wiley & Sons, Inc., 2002)
A guidebook for mental health professionals on how to assess whether a client is at risk for suicide. It offers clinicians a sensitive interviewing strategy to determine lethal risk.
Includes bibliographical references and index.
Keywords: Suicide -- Risk factors; Suicide -- Prevention; Suicide -- prevention and control